Formation of partial κ-Ce2Zr2O8 phase and its promotion on the supported Pd-only three-way catalysts. (September 2021) - Deng, Jie; Chen, Yusheng; Li, Mengchen; Li, Shanshan; Jiao, Yi; Wang, Jianli; Chen, Yaoqiang
Graphical abstract: The presence of partial κ -Ce2 Zr2 O8 phase in CeO2 -ZrO2 (CZ) support strengthened Pd-CZ interaction, providing a route to generate highly reactive Pdδ + (δ ≥ 3) at the Pd-CZ interfaces and immobilize Pd nanoparticles through Pd-O-Ce bonds. After thermal aging, Pd/950ROa showed smaller PdOx nanoparticles and larger amount of highly reactive Pdδ +, which is responsible for its superior catalytic activity for NO and C3 H8 conversion. Highlights: The CeO2 -ZrO2 -based nanomaterial with active κ -Ce2 Zr2 O8 phase and sufficient specific surface area was synthesized. A handful of κ -Ce2 Zr2 O8 nano-domains can enhance the reducibility of CeO2 -ZrO2 -based nanomaterial considerably. The presence of partial κ -Ce2 Zr2 O8 strengthens metal-support interaction, consequently immobilize Pd nanoparticles. The highly reactive Pd δ+ (δ ≥ 3) at Pd-CZ interfaces accelerates the conversion of NO and C3 H8 . Abstract: Severe air pollution is pushing towards developing more efficient three-way catalysts (TWCs), especially for the elimination of NO and C3 H8 . In this work, the highly active κ -Ce2 Zr2 O8 phase was investigated and introduced into TWCs. First, we demonstrated that the cation-ordered pyrochlore-type structure was formed during severe reduction, accompanied by a Zr-rich surface as detected by CH3 OH-FTIR. Although only partial κ -Ce2 Zr2 O8 nano-domains were observed by HRTEM, which nucleated within the fluorite matrix of CZ-950RO, they acted as a blasting fuse to boost the whole reduction. Moreover, the presence of κ -Ce2 Zr2 O8 phase strengthened Pd-CZ interaction, providing a route to generate highly reactive Pdδ + (δ ≥ 3) and immobilize palladium nanoparticles through Pd-O-Ce bonds as evidenced by XPS and CO chemisorption. Thanks to the strengthened Pd-CZ interaction, Pd/950RO exhibited a stable activity toward NO and C3 H8 conversion.